Peningkatan Karakter Dan Kedisiplinan Siswa MA Tarbiyatul Banin Banat Melalui Kegiatan Apel Pagi - Alfian Mubaidilla, Irfa’i; Fitriyah, Jamilatul; Lailatul Khoiriyah, Siti (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2024)
This research aims to explain the formation of character and manners in students through morning assembly activities and their effectiveness in realizing good character and manners in students at MA Tarbiyatul Banin Banat Jetak. The type of research used is qualitative research with a qualitative descriptive method. The data in this research was obtained through observation activities. The subjects in this research were students and teachers at MA Tarbiyatul Banin Banat Jetak. Based on the research conducted, the results showed that the morning assembly activity at MA Tarbiyatul Banin Banat Jetak can be used as an effective means and way to shape and instill character and manners in children such as discipline, responsibility, politeness, and mutual respect for fellow students. and respect teachers.